Intelligent learning environment: Building hybrid system from standard application and web application - Chee, , KS; Phon-Amnuaisuk, , S (2005)
In this paper, we explore the idea of Intelligent Learning Environment (ILE) by building a system for teaching and learning music in a web-based environment. Our system is a framework that utilises existing web architecture. Instead of using a standard web browser as our client tool, we are going to develop our own. By following this, some design issues regarding the shifting and their solutions will be addressed. In a nutshell, this environment allows us to gain more control in monitoring students' learning activities within a single environment while keeping instructors away from a bundle of computer codes.